The probability of poverty for mothers after childbirth and divorce in Europe: The role of social stratification and tax-benefit policies - Daria Popova; Jekaterina Navicke (University of Essex, Institute for Social and Economic Research (ISER), 2019)
This paper looks at the effects of tax-benefit systems and social stratification determinants on the probability of poverty among mothers after childbirth and divorce/separation. The analysis was carried out for twelve EU countries, which represent a variety of welfare regimes providing different degrees of defamilialisation. We applied the stress-testing methodology using microsimulation techniques as proposed by Atkinson (2009) and carried out a regression analysis of the simulated results. We show that the degree of income replacement provided by the welfare state is higher for childbirth than for divorce. Countries with low post-childbirth poverty include those with an explicit pro-natalist orientation and socio-democratic regimes. High post-childbirth poverty rates are found in pro-traditional and South European conservative countries, and especially in the liberal regimes. The same is true for the post-divorce poverty rates. Moreover, our findings confirm that the mother's occupational class has a statistically significant effect for predicting poverty in the case of both events, with a stronger social gradient in case of divorce. Cross-country variation in the social gradient for post-childbirth poverty was insignificant. For post-divorce poverty we find weaker social class effects in the highly defamilialised welfare systems (Scandinavian countries and France) and stronger social class effects in the UK and the post-socialist countries.
Keywords: I32; I38; J18; 330; welfare state; life-course event; stratification; poverty; childbirth; parental separation; divorce; Europe